A hierarchical model for critical success factors in apparel supply chain. Issue 7 (10th April 2020) - Chowdhury, Nighat Afroz; Ali, Syed Mithun; Paul, Sanjoy Kumar; Mahtab, Zuhayer; Kabir, Golam
Abstract : Purpose: Supply chain management plays an important role in sustaining businesses in today's competitive environment. Therefore, industrial managers are focusing on exploring the key performance improvement attributes of supply chain management to achieve a better position in the global market. Aimed at ensuring best supply chain management practices, this study presents the key performance improvement attributes, known as critical success factors (CSFs), within the context of the apparel supply chain of Bangladesh. Design/methodology/approach: In this paper, the interpretive structural modeling method (ISM) has been applied to develop a structural framework to analyze the contextual relationship among the factors under consideration. MICMAC (Matriced' Impacts Croise´s Multiplication Applique´e a´ unClassement) analysis has also been performed to define the classification of the CSFs in terms of their driving and dependence power. Findings: The research findings reveal that supply chain collaboration/partnership and customer satisfaction are of crucial importance to success in the context of supply chain management of the readymade (RMG) garments industry of Bangladesh. Further evidence suggests that these, along with other success factors, can assist in achieving a competitive advantage and better market position. A number of theoretical and managerial implications have been provided for managers and practitioners, and for further evaluation of the study. Originality/value: This paper considers a new supply chain problem which identifies and evaluates critical success factors. This paper also develops a new structural model for evaluating critical success factors.